2018
DOI: 10.1111/josi.12269
|View full text |Cite
|
Sign up to set email alerts
|

“I Have a Dream” of a Colorblind Nation? Examining the Relationship between Racial Colorblindness, System Justification, and Support for Policies that Redress Inequalities

Abstract: One of Dr. Martin Luther King's most memorable quotes came from his famous "I have a dream" speech, which arguably called for a racially colorblind society. Today, colorblindness represents a complex ideology used in education, businesses, and governments, with both positive and negative implications for intergroup relations. On the one hand, colorblindness is used to promote fairness and equality between groups by asking people to ignore group membership and treat everyone the same. On the other hand, colorbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…In particular, more research involving larger samples of individuals who identify with three or more stigmatized groups is needed, as is more research involving a variety of designs, including experimental work. In addition, more work situated in cultures outside of the United States is needed in order to understand cultural influences on multiple stigmatization (e.g., Yogeeswaran, Verkuyten, Osborne, & Sibley, ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, more research involving larger samples of individuals who identify with three or more stigmatized groups is needed, as is more research involving a variety of designs, including experimental work. In addition, more work situated in cultures outside of the United States is needed in order to understand cultural influences on multiple stigmatization (e.g., Yogeeswaran, Verkuyten, Osborne, & Sibley, ).…”
Section: Discussionmentioning
confidence: 99%
“…A central claim made by system justification theory is that people endorse system‐justifying beliefs – beliefs that legitimize, defend, and reinforce the status quo – in order to satisfy their epistemic, existential, and relational needs (Hennes et al ., ; Jost & van der Toorn, ). Accordingly, many belief systems have been argued to support the status quo including the protestant work ethic (Jost et al ., ), meritocracy (Jost, Pelham, Sheldon, & Sullivan, ; Sengupta & Sibley, ; Tan, Liu, Huang, & Zheng, ), belief in a just world (Jost & Burgess, ), colour‐blind ideology (Yogeeswaran, Verkuyten, Osborne, & Sibley, ), and conservatism (see Jost & Hunyady, ). Because the core aspects of a conservative belief system focus on opposition to change and acceptance of inequality (Jost, ), conservatism is ‘a prototypical system‐justifying ideology’ (Jost, Blount, Pfeffer, & Hunyady, , p. 63) that should be particularly effective at satisfying one's epistemic, existential, and relational needs.…”
Section: Introductionmentioning
confidence: 99%
“…If there is evidence that color-blind conceptions of school diversity are a tool for justifying practices that might be perceived as racialized (picking whiter schools), it suggests that the ambiguity and malleability of the term diversity affords individuals the opportunity to "ignore" racialized practices involving schools. Language matters and in certain situations-such as when working to redress racial segregation-not specifically referencing race allows racism to persist because no one 470 Petts person or institution is found to be at fault (Mueller 2017;Perez and Salter 2019;Yogeeswaran et al 2018). A study in one California school found that because administrators were silent about race when talking publicly about issues in the school, there was no easy way to handle school racial inequalities (Pollock 2009).…”
Section: Consequences Of How Diversity Is Understoodmentioning
confidence: 99%